2003
DOI: 10.1007/s00421-003-0825-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on skin and muscle blood flow in healthy subjects

Abstract: In 14 healthy female subjects, the effects of needle stimulation (acupuncture) on skin and muscle blood flow were investigated using a non-invasive custom-designed probe and photoplethysmography (PPG). In randomised order, 2-7 days apart, three modes of needle stimulation were performed on the anterior aspect of the tibia: superficial insertion (SF), insertion into the anterior tibial muscle (Mu), and insertion into the muscle including manipulation of the needle in order to elicit a distinct sensation of dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(146 citation statements)
references
References 22 publications
(38 reference statements)
5
136
1
2
Order By: Relevance
“…The mechanism underlying increased blood flow by acupuncture has been suggested to rely on the activation of thin nerve fibers, which release vasoactive neuropeptides and NO from their peripheral terminals upon activation; this leads to vasodilatation and increased blood flow [1,102,103]. It is noted that because NO is involved in multiple body functions, its presence in the peripheral blood or in an acupuncture point is supportive of our hypothesis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The mechanism underlying increased blood flow by acupuncture has been suggested to rely on the activation of thin nerve fibers, which release vasoactive neuropeptides and NO from their peripheral terminals upon activation; this leads to vasodilatation and increased blood flow [1,102,103]. It is noted that because NO is involved in multiple body functions, its presence in the peripheral blood or in an acupuncture point is supportive of our hypothesis.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have provided a variety of information regarding the physiological effects of acupuncture on animal and human bodies. Most of them have indicated that acupuncture is able to increase blood flow [1], and at the acupuncture points and meridians have a high electrical conductance [2,3]. A relationship has also been suggested that among those acupuncture points and meridians with connective tissue planes [4] and the perivascular space [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that C-fibre activation evokes an ~5-s delay from the onset of AS at a very low (1 Hz) frequency of stimulation (Ochoa & Torebjork, 1989). The long-lasting effects, even after the termination of stimulation where the needle remains stationary, on hyperoxygenation indicate that vasoactive substances such as calcitonin gene-related peptide (CGRP) from the sensory nerve terminals are involved in the mechanisms (Sandberg et al, 2003). In this study, it is suggested that vasodilative substances induced by AS, mediated by the axon reflex via polymodal receptors in the skeletal muscle and the skin, played a role in the local muscle oxygenation response to the stimulation.…”
Section: The Effects Of Acupuncture and Moxibustionmentioning
confidence: 85%
“…It is believed that shoulder stiffness is caused primarily by restriction of blood flow to the working muscles where accumulated metabolites appear to activate sympathetic vasoconstrictors. Acupuncture stimulation (AS) is reported to increase local tissue blood flow in animals (Noguchi et al, 1999;Sato et al, 2000;Uchida et al, 2007) and humans (Sakai 2005;Sandberg et al, 2003;Sandberg et al, 2005) and are applicable in therapeutic interventions of shoulder stiffness. The effects of acupuncture include neural, endocrinological, cardiovascular, and immunological functions.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] Local needling produces analgesic effects in areas of injury by locally increasing the blood supply through the release of vasodilatory neuropeptides and thereby increasing local oxygen and cytokines along with reducing inflammation. 26,27 Acupuncture also has been indicated as having a positive therapeutic effect on other mTBI-related symptoms such as headaches, neck pain, and nausea. [28][29][30][31] Because of the prevalent nature of mTBI injuries, there is need for additional treatment protocols to be available for injuries sustained by adults in nonathletic situations.…”
Section: Introductionmentioning
confidence: 99%